Food antigens suppress small intestinal tumorigenesis - Sasaki, Takaharu; Ota, Yuna; Takikawa, Yui; Terrooatea, Tommy; Kanaya, Takashi; Takahashi, Masumi; Taguchi-Atarashi, Naoko; Tachibana, Naoko; Yabukami, Haruka; Surh, Charles D.; Minoda, Aki; Kim, Kwang Soon; et al. (Frontiers in Immunology, 2024)
Food components suppressing small intestinal tumorigenesis are not well-defined partly because of the rarity of this tumor type compared to colorectal tumors. Using Apcmin/+ mice, a mouse model for intestinal tumorigenesis, and antigen-free diet, we report here that food antigens serve this function in the small intestine. By depleting Peyer’s patches (PPs), immune inductive sites in the small intestine, we found that PPs have a role in the suppression of small intestinal tumors and are important for the induction of small intestinal T cells by food antigens. On the follicle-associated epithelium (FAE) of PPs, microfold (M) cells pass food antigens from lumen to the dendritic cells to induce T cells. Single-cell RNA-seq (scRNA-seq) analysis of immune cells in PPs revealed a significant impact of food antigens on the induction of the PP T cells and the antigen presentation capacity of dendritic cells. These data demonstrate the role of food antigens in the suppression of small intestinal tumorigenesis by PP-mediated immune cell induction.